Initial Carbon−Carbon Bond Formation during the Early Stages of Methane Dehydroaromatization - Çağlayan, Mustafa; Lucini Paioni, Alessandra; Abou‐Hamad, Edy; Shterk, Genrikh; Pustovarenko, Alexey; Baldus, Marc; Chowdhury, Abhishek Dutta; Gascon, Jorge (Angewandte Chemie International Edition, 2020)
Methane dehydroaromatization (MDA) is among the most challenging processes in catalysis science owing to the inherent harsh reaction conditions and fast catalyst deactivation. To improve this process, understanding the mechanism of the initial C−C bond formation is essential. However, consensus about the actual reaction mechanism is still to be achieved. In this work, using advanced magic‐angle spinning (MAS) solid‐state NMR spectroscopy, we study in detail the early stages of the reaction over a well‐dispersed Mo/H‐ZSM‐5 catalyst. Simultaneous detection of acetylene (i.e., presumably the direct C−C bond‐forming product from methane), methylidene, allenes, acetal, and surface‐formate species, along with the typical olefinic/aromatic species, allow us to conclude the existence of at least two independent C−H activation pathways. Moreover, this study emphasizes the significance of mobility‐dependent host–guest chemistry between an inorganic zeolite and its trapped organic species during heterogeneous catalysis. The initial C−C bond formation during the early stages of methane dehydroaromatization was investigated by employing “mobility‐dependent” solid‐state NMR spectroscopy. Based on the detected species (such as acetylene, acetal etc.) at least two different mechanisms (mono‐functional vs. bi‐functional) for the formation of direct C−C bonds were identified.